PENGARUH INOKULASI FUNGI MIKORIZA ARBUSKULA (FMA) PLUS ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG PADA ULTISOL - Eddiwal Eddiwal; Amrizal Saidi; Eti Farda Husin; Azwar Rasyidin (Jurnal Solum, 2018)
Mycorrhizal symbiosis increases nutrient uptake for plants, resistance to disease, stabilizes soil aggregates and promotes the growth of soil organisms. Fungal hyphae containing glomalin is essential for soil biological processes because of their interactions with plants, soils, and microbes. Activity of AMF in the area of rhizosphere and mycorizosphere will improve the physical, chemical and biological conditions of the soil, thereby providing a healthy soil environment for plants. How the influence of AMF inoculants plus organic ingredients on growth and production of maize on Ultisol needs to be tested in the field.  The purpose of this experiment is the application of AMF plus organic inoculants to corn planting, to determine the effect on growth and increase of corn production. Experiments using a randomized block design with four groups. The AMF inoculation treatment was the administration of organic plus inoculant from G. luteum (F1), G. verruculosum (F2), G. versiforme (F3), Multi species of AMF (F4) and without AMF inoculation (F0). The results showed that AMF inoculation had significant effect on total glomalin. G. versiforme has the highest total glomalin, which is 10.59 mg.g-1. The effect of AMF species had no significant effect on aggregate stability, but was significantly different from the treatment without AMF inoculation. The effect of AMF on N, P and K uptake is significantly different. The highest dry corn kiln production from G. versiforme, which is 8.07 kg / plot or 4.04 ton / ha, has the same effect as G. luteum (7.98 kg / plot or 3.99 ton / ha) and Multi AMF (7.67 kg / plot or 3.84 tons / ha). Increased production of dried corn plants inoculated with AMF plus organics can reach 40-83% higher than the plants without giving the AMF.Key words : mycorizosphere, productivity, rhizosphere, Ultisol